Cell‐specific resetting of mouse islet cellular clocks by glucagon, glucagon‐like peptide 1 and somatostatin. (18th January 2018) - Petrenko, V.; Dibner, C.
Abstract: Aim: Molecular clocks, operative in pancreatic islet cells, represent an intrinsic mechanism regulating intracellular metabolism and hormone secretion. Glucagon, somatostatin and glucagon‐like peptide 1 (GLP‐1) are essential coordinators of islet physiology. Here, we assess the synchronizing capacity of glucagon, somatostatin and GLP‐1 on pancreatic α‐ and β‐cell circadian clocks. Methods: Triple transgenic mice, expressing a circadian PER2::luciferase (luc) reporter combined with α‐ and β‐cell‐specific fluorescent reporters, were employed. Isolated pancreatic islets and fluorescence‐activated cell sorting‐separated α‐ and β‐cells were synchronized with glucagon, somatostatin analogue or GLP‐1 mimetics, with subsequent real‐time PER2::luc bioluminescence recording. Gene expression of Gcgr, Sstr2, Sstr3 and Glp1r in islet cells was assessed by RNA sequencing and RT‐qPCR. Results: Glucagon and GLP‐1 mimetics (liraglutide and exenatide) induced high‐amplitude rhythmic expression of the PER2::luc reporter in β‐cells, but not in α‐cells, while the somatostatin analogue octreotide generated a significant phase shift between α‐ and β‐cells. Enrichment of Gcgr and Glp1r transcripts was detected in β‐cells compared to their α‐cell counterparts. The synchronizing effect of glucagon was dose‐dependent and mediated by the adenylate cyclase signalling cascade, as it was diminished by adenylate cyclase inhibitor. Conclusion: We conclude that proglucagon‐derived peptides and somatostatin exhibit receptor‐mediated cell‐specific synchronizing effects for mouse α‐ and β‐cell oscillators. Differential islet cell clock modulation by glucagon and somatostatin may represent a physiological mechanism underlying paracrine regulation of rhythmic glucagon and insulin secretion. The reported here strong synchronizing properties of GLP‐1 mimetics, widely used for treatment of type 2 diabetes, are of high clinical relevance.